Family business management: A case study in the Portuguese footwear industry - Rui Silva; André Coelho; Nuno Sousa; Patrícia Rodrigues Quesado (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The family business is one of the world economy's leading drivers, playing a significant role in countries' economic and social development. Portugal is a country very dependent on this type of companies, which makes this study important, not only for discussing the problem in this scientific field but also for understanding family business characteristics in a country so dependent on this type of business. In this sense, this research work's general objective is to understand the reality of the management of family businesses in the footwear industry, through the vision of the CEO's of five companies in the North of Portugal. The present study is qualitative, as interviews were carried out with five CEOs of family businesses. The authors collected the participants' reports between June and July 2019, in a single moment, through a face-to-face interview held at their respective workplaces, after prior scheduling. The interviews were recorded using an audio recorder and later transcribed and imported for analysis. The results obtained demonstrated that these organizations contribute enormously to the country's economic and social development. This study also contributes to improving the understanding of the subject under analysis, through interviews with CEOs in the footwear industry in the Northern region of Portugal, exposing in more depth this representative and emerging sector, in a country mostly characterized by family businesses. It also aims to contribute to understanding the main determinants and characteristics of family businesses in the literature, like family businesses and performance, namely, ownership, professionalization, company-family relationship, succession, management and performance practices. With this study's results, it is also expected that they may be susceptible to discussion and comparison with family businesses from other countries and from different business areas.
Keywords: 650; family business; footwear industry; management; performance; qualitative analysis